Influence of the Volleyball Training on Body Build of Girls Aged 15-17 Years. Longitudinal Study - Janusz, Antoni; Jarosińska, Aniela; Stęślicki, Jerzy (Anthropological Review, 1985)
A group of girls intensively training volleyball was compared with a control group. The examinations were repeated three times in one-year intervals. Differences in somatotypical transformations in girls of both groups were observed.